The ancient Egyptian pyramid texts - Allen, James P., 1945- (Atlanta, Georgia : SBL Press, 2015)
The pyramid texts are the oldest body of extant literature from ancient Egypt. First carved on the walls of the burial chambers in the pyramids of kings and queens of the Old Kingdom, they provide the earliest comprehensive view of the way ancient Egyptians understood the structure of the universe, the role of the gods, and the fate of human beings after death. Their importance lies in the antiquity and in their endurance throughout the entire intellectual history of ancient Egypt. This revised edition containts the complete translation of the pyramid texts and incorporates the traditional numbering system of the texts with the new numbers from the latest 2013 concordance. The revisions take into account recent advances in the understanding of Egyptian grammar and reflect the primarily atemporal verbal system of Old Egyptian that expresses the timeless quality that ancient authors understood the texts to have.
Includes bibliographical references (pages 369-373) and index.
Online resource; title from PDF title page (EBSCO, viewed August 4, 2015).
Master record variable field(s) change: 050
Keywords: Incantations, Egyptian -- Translations into English; Future life; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Comparative Religion; Future life; Incantations, Egyptian; Electronic books; Translations